2017
DOI: 10.1177/0306624x17739186
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence Assessment Instruments in Adult Prison Populations: A Systematic Review

Abstract: Detection of intellectual disability (ID) in the penitentiary system is important for the following reasons: (a) to provide assistance to people with ID in understanding their legal rights and court proceedings; (b) to facilitate rehabilitation programs tailored to ID patients, which improves the enhancement of their quality of life and reduces their risk of reoffending; and (c) to provide a reliable estimate of the risk of offence recidivism. It requires a short assessment instrument that provides a reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…First, a semistructured clinical interview is conducted, followed by the Personality Assessment Inventory (PAI), which has demonstrated high construct validity (Slavin-Mulford et al, 2012). Staff then assess intellectual functioning using the Beta-4, a common intelligence test in correctional settings (van Esch et al, 2018). In addition to these assessments, there is a review of prison records and consultation with psychiatry staff.…”
Section: Administrative Data On Solitary Confinementmentioning
confidence: 99%
“…First, a semistructured clinical interview is conducted, followed by the Personality Assessment Inventory (PAI), which has demonstrated high construct validity (Slavin-Mulford et al, 2012). Staff then assess intellectual functioning using the Beta-4, a common intelligence test in correctional settings (van Esch et al, 2018). In addition to these assessments, there is a review of prison records and consultation with psychiatry staff.…”
Section: Administrative Data On Solitary Confinementmentioning
confidence: 99%
“…Three of these used K-BIT, the Vineland Adaptive Behaviour Scale (VABS) and Wechsler Adult Intelligence Scale (WAIS) (Hayes, 2005;Hayes, 2002;Hayes and Farnill, 2003). In most studies involving K-BIT, participants were children (van Esch et al, 2018).…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…It is a well-validated measure of basic cognitive functioning across culturally and ethnically groups (Raven, 2000). Studies also report its use as a short assessment tool of 30 items (Van der Elst et al, 2013;Creed et al, 1999), and that, as early as 1992, it was validated (normed) with a prisoner population (van Esch et al, 2018). Using Ravens in a forensic setting (Habets et al, 2015) found moderate correlation between Raven's scores with WAIS-111.…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…Knowledge of an individual’s LD should assist staff and other key professionals such as the Parole Board in tailoring their communication, to ensure accessibility of understanding for the individual. However, the challenges of identifying individuals in prison, who have LD continues to be acknowledged (Board et al , 2015; vanEsch et al , 2018). Hayes (2007) summarised a number of these challenges including uncertainty around the prevalence of LD and lack of knowledge about LD across the criminal justice system (CJS).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to be more predictive of whether someone has an LD, when compared with WAIS-III (Mckenzie et al , 2012), and to be feasible for use in prisons (Murphy et al , 2017). Other tools include the Raven’s Standard Progressive Matrices (RSPM; Raven, 1941) comprising 60 items designed to test abstract reasoning, which is considered a relatively good measure of general intelligence, suitable for non-native speakers (vanEsch et al , 2018). The Hayes Ability Screening Index (HASI; Hayes, 2000) has been identified as a quick and practical tool, validated for use within forensic settings (Sondenaa et al , 2008).…”
Section: Introductionmentioning
confidence: 99%